Honeydew melon production in Iloilo prospects and potentials - Olido, Celso C. (2003)
The study was conducted to determine the prospects and potentials of honeydew melon production in the province of Iloilo, The descriptive-qualitative research highlights the socio-economic profile of the honeydew melon farmers, the historical development, the status, the marketing situation, and the problems, issues and other concern regarding honeydew melon industry as a whole. Only 13 out of 24 respondents qualified as sources of numerical profiles, only Oton and San Miguel were identified as honeydew melon producing areas in the province. Interview results revealed that as early as 1982, commercial production of honeydew melon had started at Sitio Bongol, Barangay Cabuloan Norte, Oton. Though it is labor intensive and a considerable amount of chemical inputs were used for production, a mean net income of â‚±80,000.25 per hectare of honeydew melon was attained by the farmers in 2003 ad the return on investment (ROI) ranged from 215% to 312% during a regular season planting (1999-2003). The farmers attributed the good profitability to fertile soil and favorable climate of the province. There is also a big potential for the industry to absorb surplus labor as daily cultural management activities requires services of hired laborers. in terms of technology, the farmers have developed the technology for honeydew melon through their experience on watermelon production. Strategically, Iloilo province has a trade accessibility advantage with the presence of its port that serves as transit point for transporting and marketing honeydew melon to other key cities locally or abroad. There exists a bright prospect for export as shown by one of the pioneers of production who experienced exporting honeydew with a Taiwanese financier way back in 1996. to 1998. Another great opportunity for the country lies in the production of honeydew melons because the Philippines is geographically much closer to Hong Kong, a large consumer of honeydew melon, than other countries that export it to the former colony (Frohmader, 2000). Considering its potentials for local and export market, the prospects of a better income and opportunities for job generation as well as its' adaptability to local condition, there is an urgent need for a government initiated program that will provide technical, financial and marketing assistance to the honeydew farmers in order to develop the industry. Production should be expanded to other municipalities while R & D on off-season production must be a priority measure to ensure continuity of supply and gain better market accessibility. Integrated pest management (IPM) program must be availed of by the honeydew melon farmers to minimize, if not totally eradicate the advent use of chemicals. Market-oriented production and market matching must be done to assist the farmers in marketing and minimize exploitation from traders. Export market should be a definite area of concern for market expansion as a contributory move towards the governments' objective of global competitiveness.
Research Study (Mgt 299-Research Methods in Management). -- [Iloilo city] : UPV-CM, June 2003.